ANALYSIS OF FACTORS INHIBITING THE DEVELOPMENT OF COOPERATIVE STUDENTS OF BINA BEURATA FACULTY OF ECONOMICS UNIVERSITAS MALIKUSSALEH - Rahmaniar Rahmaniar (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
This study aims to analyze the influence of internal factors and external factors to hinder the development of cooperatives. This study uses primary data in the form of a 2020 weekly report which is accessed on www.indodax.com.The method of internal data analysis is research data obtained directly from the original source which is carried out using a questionnaire that is processed using SPSS 20 (Statistical Package For Social Science). The results of the study partially show thatInternal factors have a significant effect on inhibiting the development of the Bina Beurata Student Cooperative, Faculty of Economics, Universitas Malikussaleh. External factors have a significant effect on inhibiting the development of the Bina Beurata Student Cooperative, Faculty of Economics, Universitas Malikussaleh. Variable internal factors and external factors in inhibiting the development of cooperatives is 0.362 or 36.2%, while the remaining 63.8% is influenced by other variables not included in this study